2020
DOI: 10.1038/s41598-020-72998-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among Chinese university students: a systematic review and meta-analysis

Abstract: Estimates of the depression prevalence among Chinese university students vary considerably across studies. This systematic review and meta-analysis aimed to comprehensively analyze the depression prevalence among Chinese university students. We searched four electronic databases with the search terms of depression, China, university student, and questionnaire. Studies reporting depression among Chinese university students were included in the analysis. Two reviewers independently extracted the data and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 27 publications
2
77
3
3
Order By: Relevance
“…Common mental problems of college students include depression, compulsion, anxiety and interpersonal sensitivity [12][13][14][15]. Two recent systematic reviews found a prevalence of depression of 28.4% in Chinese college students, compared with 25% of postgraduate students suffering from mental illness [16,17]. Therefore, understanding the prevalence and predictors associated with college students' mental health could help to develop effective psychological interventions and reduce related adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Common mental problems of college students include depression, compulsion, anxiety and interpersonal sensitivity [12][13][14][15]. Two recent systematic reviews found a prevalence of depression of 28.4% in Chinese college students, compared with 25% of postgraduate students suffering from mental illness [16,17]. Therefore, understanding the prevalence and predictors associated with college students' mental health could help to develop effective psychological interventions and reduce related adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, youth depression is a major risk factor for suicide (Majeed and Lee, 2017). University students experience depression at a significantly higher rate than the general population, and also higher than their non-college contemporaries (Bayram and Bilgel, 2008;Lei et al, 2016;Gao et al, 2020). However, negative attitudes and beliefs (stigma) toward people with depression are common.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 47% of the university students suffered from different kinds of psychological problems, according to a national survey on the psychological well-being of Chinese university students in 2019 conducted by Dingxiangyuan and China Youth Daily ( 34 ). The meta-analysis study showed that the prevalence of depression among Chinese students ranged from 3 to 80.6% ( 35 ). The percentage of U.S. college students with a diagnosed mental health condition increased from 21.9% in 2007 to 35.5% in 2016–2017 ( 36 ).…”
Section: Introductionmentioning
confidence: 99%